Evaluating the reporting of adverse events in controlled clinical trials conducted in 2010–2015 on migraine drug treatments. (October 2018) - Tfelt-Hansen, Peer; Lindqvist, Janus Kaufmann; Do, Thien Phu
Background: In 2008, the International Headache Society published guidelines on the "evaluation and registration of adverse events in clinical drug trials on migraine". They listed seven recommendations for reporting adverse events in randomized controlled trials on migraine. The present study aimed to evaluate adherence to these recommendations, and based on the results, to recommend improvements. Methods: We searched the PubMed/MEDLINE database to identify controlled trials on migraine drugs published from 2010 to 2015. For each trial, we noted whether five of the recommended parameters were presented. In addition, we noted whether adverse events were reported in abstracts. Results: We identified 73 trials; 51 studied acutely administered drugs and 22 studied prophylactic drugs for migraine. The number of patients with any adverse events were reported in 74% of acute-administration and 86% of prophylactic drug trials. Only 30 (41%) of the 73 studies reported adverse events with data in the abstracts, and 27 (37%) abstracts did not mention adverse events. Conclusion: Adverse events, both frequency and symptoms, should be reported to allow a fair judgement of benefit/tolerability ratio when randomized controlled trials in migraine treatment are published. Clinically significant adverse events should be included in the abstract of every randomized controlled trial in migraine treatment.